Financial Incentives for Chronic Disease Management: Results and Limitations of 2 Randomized Clinical Trials With New York Medicaid Patients. Issue 7 (September 2018) - VanEpps, Eric M.; Troxel, Andrea B.; Villamil, Elizabeth; Saulsgiver, Kathryn A.; Zhu, Jingsan; Chin, Jo-Yu; Matson, Jacqueline; Anarella, Joseph; Roohan, Patrick; Gesten, Foster; Volpp, Kevin G.
Purpose: To identify whether financial incentives promote improved disease management in Medicaid recipients diagnosed with hypertension or diabetes, respectively. Design: Four-group, multicenter, randomized clinical trials. Setting and Participants: Between 2013 and 2016, New York State Medicaid managed care members diagnosed with hypertension (N = 920) or with diabetes (N = 959). Intervention: Participants in each 6-month trial were randomly assigned to 1 of 4 arms: (1) process incentives—earned by attending primary care visits and/or receiving prescription medication refills, (2) outcome incentives—earned by reducing systolic blood pressure (hypertension) or hemoglobin A1c (HbA1c ; diabetes) levels, (3) combined process and outcome incentives, and (4) control (no incentives). Measures: Systolic blood pressure (hypertension) and HbA1c (diabetes) levels, primary care visits, and medication prescription refills. Analysis and Results: At 6 months, there were no statistically significant differences between intervention arms and the control arm in the change in systolic blood pressure, P = .531. Similarly, there were no significant differences in blood glucose control (HbA1c ) between the intervention arms and control after 6 months, P = .939. The majority of participants had acceptable systolic blood pressure (<140 mm Hg) or blood glucose (<8.0%) levels at baseline and throughout the study. Conclusion: Financial incentives—regardless of whether they were delivered based on disease-relevant outcomes, process activities, or a combination of the two—have a negligible impact on health outcomes for Medicaid recipients diagnosed with either hypertension or diabetes in 2 studies in which, among other design and operational limitations, the majority of recipients had relatively well-controlled diseases at the time of enrollment.